Analisis Kandungan Zat Besi pada Roti Tawar Subtitusi Tepung Sorgum - Kartika Dewi Sukmawati; Eva Silviana Rahmawati; Dian Ayu Ainun Nafies (Yayasan Literasi Sains Indonesia, 2024)
Iron deficiency anemia is a hematological disease that is often found in pregnant women. This situation can certainly hinder the growth and development of the fetus in pregnant women. It can be said to be anemia if the number of red blood cells or hemoglobin is below the normal limit if the hemoglobin level is <14 g/dL in men and <12g/dL in women. The aim of this research is to determine the effect of sorghum flour substitution on the iron content of white bread. This research used a True Experimental with Completely Randomized Design (CRD), 4 treatment levels and 6 replications. The treatment applied was the ratio of wheat flour: sorghum flour at P0 (100:0), P1 (30:70), P2 (20:80), P3 (10:90), respectively. The results showed an increase in iron levels in white bread substituted for sorghum flour. The higher the sorghum flour formulation added to white bread, the higher the iron content in the white bread.